Captivity and empire: Russian captivity narratives in fact and fiction - Gao, Yuan (Nazarbayev University School of Sciences and Humanities, 2016)
This thesis studies Russian captivity narratives about Central Asia produced during the nineteenth century. Focusing on the captivity theme, this thesis explores diverse individual captivity stories written within the grand context of Russia’s expansion into Central Asia. It aims to show that captivity narratives not only tell of the vulnerability and uncertainty of the empire during its expansion, but also reveal the rapid shift of power in Central Asia in the nineteenth century. They witness Russian captives’ growing awareness of Central Asia as a site of Russia’s future colonization, and the captives’ self-awareness of their Russian and imperial identity...
Тұтқындық және империя: шын деректердегі және көркем әдебиеттегі орыс тұтқындық хикаялары
Плен и империя: русские нарративы о плену в фактах и в художественной литературе
Keywords: captivity; empire; Russian captivity; тұтқындық; империя; орыс тұтқындық хикаялары; плен; русские нарративы; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Literature